Extension of BET theory to CO2 adsorption isotherms for ultra-microporosity of covalent organic polymers - Mukhtar, A. (Springer Nature, 2020)
Usually, nitrogen and argon adsorptionâdesorption isotherms are used at their respective boiling points for the determination of specific surface area via the BET theory of microporous materials. However, for ultra-micropores, where nitrogen and argon cannot access at cryogenic temperatures, the CO2 adsorptionâdesorption isotherms have been considered as alternative options for the determination of specific surface area by extending BET theory, but the surface area determined by using CO2 adsorptionâdesorption isotherms is not significant due to strong CO2-CO2 interactions. In this study, the microporous covalent organic polymers are subjected to nitrogen and CO2 adsorptionâdesorption isotherms and the results showed that a clear linear region is available in isotherms, which confirms the presence of ultra-micropores. The surface area determined by the CO2 adsorptionâdesorption isotherms is higher than the surface area determined by N2 adsorptionâdesorption isotherms. These results indicate that the microporous covalent organic polymers contain ultra-micropores where only CO2 can reach, while nitrogen and argon cannot access at cryogenic conditions because their kinetic diameter is larger than CO2. Â© 2020, Springer Nature Switzerland AG.